The Graying of the Digital Game Market in the Greater China Region: A Computational Framing Analysis of Media Discourses - Kang, Yowei; Yang, Kenneth C. C. (Intercultural Communication Studies, 2026)
The Graying of the Digital Game Market in the Greater China Region: A Computational Framing Analysis of Media Discourses